Kant against Herder. A brief analysis of an aesthetical dispute about Shakespeare - Sílvia, (Con-Textos Kantianos. International Journal of Philosophy, 2024)
Abstract. Kant’s theory of artistic genius, as formulated in the Critique of Judgment, presents a parsimonious analysis of artistic examples and an eloquent absence – Shakespeare. Cutrofello (2007) and Zammito (1992) interpreted Kant’s silence regarding Shakespeare in the Third Critique by maintaining that Kant’s attitude should be taken as a rejection of Herder’s philosophy as well as Sturm und Drang aesthetic positions. Our article refutes these readings by showing that the divide between Aufklärung and Sturm und Drang cannot be adequately invoked to understand the absence of Shakespeare in the Third Critique: accordingly, we shall analyse the aesthetic theories of Lessing, the Aufklärer, concerning Shakespeare, as these theories form the beginning of the Geniezeit in the German context; we shall also comment on a passage by Kant about Shakespeare from Vorlesungen über Anthropologie, emphasising that the affinities between Kant and Sturm und Drang regarding Shakespeare (and other poets) should be thoroughly considered.